Hemodynamically significant prosthesis‐patient mismatch can be predicted and is associated with early prosthetic valve dysfunction in aortic bioprosthesis. Issue 6 (15th May 2021) - Ronderos, Ricardo; Politi, María Teresa; Mahia, Mariana Cecilia; Castro, María Florencia; Sciancalepore, Agustina; Cueva Torres, Franklin; Kuschnir, Paola; de la Paz Ricapito, María; Vrancic, Juan Mariano; Camporrotondo, Mariano; Piccinini, Fernando; Navia, Daniel
Abstract: Objectives: To evaluate the accuracy of predicted prosthesis‐patient mismatch (PPM) regarding actual PPM measured postoperatively. To assess the association between PPM and prosthetic valve dysfunction. Methods: Retrospective cohort study including adult patients after aortic valve replacement surgery with a biological prosthesis. Predicted PPM status was determined using mean reference effective orifice area indexed to total body surface (iEOA), without considering reference standard deviations. Postoperative PPM status was determined by measuring iEOA within the first 60 postoperative days. Prosthetic valve dysfunction was defined as thrombosis, pannus, valve degeneration, and/or disruption. Results: 205 patients were enrolled between January 2003 and June 2017: predicted PPM was absent in 52 patients (25.4%), moderate in 137 patients (66.8%), and severe in 16 patients (7.8%). After surgery, the actual postoperative iEOA was measured: 53 (25.9%) did not have PPM, 73 had moderate PPM (35.6%), and 79 had severe PPM (38.5%). Predicted PPM identified the presence of hemodynamically significant actual postoperative PPM (OR = 2.56; 95%CI 1.30–5.05; P  = .006), though not its degree of severity. Prosthetic valve dysfunction was more frequent among patients with hemodynamically significant PPM (53.9% vs. 11.3%; P  < .001), compared to those without PPM. The association between PPM and prosthetic valve dysfunction was maintained after adjusting for gender, age, and ever‐smoking (OR = 9.03; P  < .001). The incidence of thrombosis or pannus was also nonsignificantly higher in patients with moderate or severe PPM. Conclusions: Predicted PPM identifies the presence, possibly not the severity, of actual postoperative PPM. Moderate or severe PPM is associated with prosthetic valve dysfunction. Actual postoperative prosthesis‐patient mismatch measured within 60 postoperative days showed a distinctive hemodynamic profile and presented a stronger association with prosthetic valve dysfunction than predicted prosthesis‐patient mismatch. A. Echocardiographic follow‐up in patients according to the actual postoperative PPM measured within 60 postoperative days. B. Prediction of prosthetic valve dysfunction based on preoperative predicted PPM or on actual postoperative PPM within 60 postoperative days. PPM: prosthesis‐patient mismatch. OR: Odds ratio.